2022
DOI: 10.3389/fcomm.2022.900257
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Social Anxiety on the Relationship Between Social Media Use and Body Dissatisfaction Among University Students

Abstract: Body dissatisfaction has become increasingly common among women and young adults and has only become worse in the digital age, where people have increased access to social media and are in constant competition and comparisons with their “friends” on their different social media platforms. While several studies have looked at the relationship between social media and body dissatisfaction, there is an obvious dearth of empirical studies on the mediating role of social anxiety- a gap this study hoped to address. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Nowadays, people tend to share their daily lives via online platforms, inadvertently causing them to make comparisons with the lives of others. This makes people more pessimistic about their body image and standard of living, resulting in increased anxiety [ 86 ]. The nervousness caused by peer pressure on the Internet leads users to be more reluctant to communicate with others in the real world.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, people tend to share their daily lives via online platforms, inadvertently causing them to make comparisons with the lives of others. This makes people more pessimistic about their body image and standard of living, resulting in increased anxiety [ 86 ]. The nervousness caused by peer pressure on the Internet leads users to be more reluctant to communicate with others in the real world.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Moreover, compared with traditional communication methods, such as phone calls and text messages, the Internet helps people to establish a much wider social network and achieve effective remote communication at a lower cost, as well as with greater efficiency [ 69 , 70 , 90 , 101 ]. Nevertheless, other studies reveal that Internet usage may distract people’s attention [ 10 , 11 , 65 , 66 , 83 ], reduce their social skills [ 47 , 67 , 68 , 84 , 85 ], and may even increase negative emotions [ 10 , 11 , 53 , 73 , 86 ]. The impact of Internet usage in this aspect would hinder interpersonal communications.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…This has worsened in the digital age, where adolescents have greater access to social media and are constantly comparing themselves to others and to unrealistic role models on various social media platforms [29]. Social expectations, promoted by social media, have been related to the onset of risk factors for eating disorders, especially during adolescence [30]. Menstrual irregularities due to different mechanisms are strongly associated with the presence of eating disorders [31].…”
Section: Discussionmentioning
confidence: 99%
“…Different scholars have offered different perspectives on the explanation of the correlation between appearance anxiety and social anxiety. Some scholars have suggested that appearance anxiety may also be triggered by social anxiety [ 70 ], while others have argued that fear of negative evaluations mediates the link between appearance anxiety and social anxiety [ 71 ]. Additionally, previous studies have found that self-compassion [ 72 ], perfectionism [ 73 ], and social rejection sensitivity [ 21 ] are also present and work to produce a relationship between the two.…”
Section: Discussionmentioning
confidence: 99%